A new modified neuroendoscope technology to remove severe intraventricular haematoma. (29th July 2018) - Du, Bo; Shan, Ai-Jun; Peng, Yu-Ping; Wang, Jin; Peng, Kai-Wen; Zhong, Xian-Liang; Zhang, Yujuan
ABSTRACT: Background : Minimally invasive endoscopic haematoma evacuation is widely used in the treatment of intraventricular haemorrhage. However, its technique still has room for improvement. A new modified neuroendoscope technology (MNT) was used in this study and we explored its safety and efficacy in the treatment of severe acute intraventricular haemorrhage by comparing it with extraventricular drainage plus urokinase thrombolytic (EVD + UT) therapy. Methods : The following parameters were compared between the MNT group and the control group: incision design, operation time, ICU monitoring time, ventricular drainage tube (VDT) placement time, post-operative drainage tube obstruction (PDTO) rate, post-operative complications rate, 6-month mortality and Glasgow Outcome Scale (GOS). Results : A total of 85 patients were enrolled. The ICU monitoring times, VDT placement times, PDTO rate were shorter in the MNT group. Multivariable logistic regression identified that good medium-term outcome (GOS scores 4–5) was significantly associated with MNT applied (OR 1.017, 95% CI 1.005–1.029, p = 0.008), age under 65 years (OR 4.223, 95% CI, 1.322–17.109, p = 0.034) and pre-operation GCS scores more than 10 (OR 3.427, 95% CI 1.048–11.205, p = 0.040). Conclusion : MNT surgery for severe intraventricular haematoma evacuation is a safe and efficient new surgical option. This technique is minimally invasive and may be helpful to provide good outcomes for selected patients.